Keefektifan Penggunaan Metode Pembelajaran SQ4R Dalam Menyimpulkan Isi Artikel Siswa Kelas XI SMAN 12 Banjarmasin - Supianur; Moh. Fatah Yasin; Dewi Alfianti (CV. ITTC INDONESIA, 2024)
Each method directs us to design learning that can help students to achieve various goals in learning. The SQ4R learning method (Survey, Question, Read, Reflect, Recite, Review) is one solution to overcome students' low reading ability. This research aims to determine the effectiveness of using the SQ4R learning method in summarizing the contents of students' articles. The sample in this research was class XI IPS at SMA Negeri 12 Banjarmasin. This research method is a quasi experiment with a nonequivalent control group design. The research sample was 30 students from class XI IPS 2 as the control class and 30 students from class XI IPS 3 as the experimental class. The independent variable is the SQ4R learning method, while the dependent variable is the ability to summarize the content of the article. Data collection uses test and non-test techniques. Data analysis techniques use descriptive and inferential analysis. The research results showed that there were differences in critical thinking abilities with an average of 81.33 from 33.83 for the experimental class and 71.67 for the control class from 34.50. The experimental class was better than the control class in training students' ability to summarize the contents of articles.